2019
DOI: 10.1007/s11082-019-2043-1
|View full text |Cite
|
Sign up to set email alerts
|

Optical polarization shift in beams emitted by quantum cascade lasers

Abstract: In this paper, we present experimental results of current-induced polarization change and transverse mode change in mid-infrared quantum cascade lasers. The polarization of laser beam was determined by measuring of far-field distributions of polarization projection on the linear polarization basis. The measured amount of TE-polarized light is associated with transversal mode structure, which was determined based on the far-field power distributions. The TE polarized light contribution in the beams varies from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…12,31,89 With the introduction of new IR instruments capable of spatial resolution beyond the diffraction limit these structures could now be analyzed with p-IR, although, the high-brightness light sources utilized in these instruments such as QCLs are inherently polarized. 103,225 This presents some minor challenges for p-IR measurements; however, it has already been shown that it is possible to perform these measurements on instruments with QCLs. 74 Furthermore, the advent of the mIRage (Photothermal Spectroscopy Corp.) instrument enables the possibility of concurrent p-IR and polarized Raman imaging at submicron spatial resolutions, producing complementary orientational maps.…”
Section: Discussionmentioning
confidence: 99%
“…12,31,89 With the introduction of new IR instruments capable of spatial resolution beyond the diffraction limit these structures could now be analyzed with p-IR, although, the high-brightness light sources utilized in these instruments such as QCLs are inherently polarized. 103,225 This presents some minor challenges for p-IR measurements; however, it has already been shown that it is possible to perform these measurements on instruments with QCLs. 74 Furthermore, the advent of the mIRage (Photothermal Spectroscopy Corp.) instrument enables the possibility of concurrent p-IR and polarized Raman imaging at submicron spatial resolutions, producing complementary orientational maps.…”
Section: Discussionmentioning
confidence: 99%
“…Its advantage comes from the many dimensions achievable by Hermite Gaussian (HG) and Laguerre (LG) modes [5]. Deterministic quantum gates also exploited the two-dimensional spatial-parity symmetry [6] of the transverse [7] single-photon field. Significant achievements raised with: temporal [8] modes and time-parity [9]; implementations coexisting [2] with traditional fibers; or orbital angular momentum (OAM) [10][5] [11].…”
Section: Introductionmentioning
confidence: 99%